Implementation to accelerate stunting reduction in Sinjai District - Firman, Firman; Alwi, Alwi; Susanti, Gita (Trigin Publisher, 2024)
Stunting is one of the main problems in the health sector. Indonesia is ranked fourth in the world and second in Southeast Asia as the country with the most stunting cases. Data from the 2019 Indonesian Toddler Nutritional Status (SSGBI) survey shows that the stunting prevalence rate in Indonesia reached 27.7% (WHO threshold of 20%). This indicates that one in four children under five in Indonesia is stunted. Children who suffer from stunting may never reach their full genetic height Children who suffer from stunting and/or wasting also suffer from weakened immunity, increased risk of death and death, and are vulnerable to long-term developmental delays. Stunting is an indicator of chronic malnutrition which is associated with negative impacts on health and cognition during childhood and continuing into adulthood. In 2020, 149 million children experienced stunting. As in previous years, the rate of decline is so slow that the global target of reducing the number of stunted children under 5 years old to 100 million by 2025 will not be achieved. Only 25% of countries can meet the UN Sustainable Development Goal (SDG) target for stunting by 2020, with the largest proportion being in the WHO region of Asia compared to less than 10% in Africa. However, for many low- and middle-income countries (LMICs) with fragile economies and majority vulnerable populations, whatever progress has been made in addressing the immediate and underlying causes of stunting, such as access to adequate nutrition for women and their babies, will have a detrimental impact.